MEDPILL: Uma Plataforma Inteligente de Controle e Monitoramento de Ingestão de Cápsulas Medicamentosas - Rodrigues , Ana Paula; Kronbauer , Artur Henrique; Araujo, Brunno (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2016: Anais Estendidos do XXII Simpósio Brasileiro de Sistemas Multimídia e Web, 2016)
The MedPill aims to help elderly people who need to manage different medications at different times. The box bear up four types of drugs and may be loaded with a maximum of 15 caps of each sort. In addition to the box, the project has two components: a bracelet and an application for smartphones. The bracelet is responsible for signaling the time taking each medication. To this end, it has a WIFI ESP8266 module configured in LUA. The application is developed in HTML, JavaScript and XML Intel XDK platform that will generate installers for various operating systems: Android, iOS, Windows Phone, Blackberry, among others. It will be responsible to set the initial settings and replenishment of the box, inform the caregiver as the amount of inventory on available medication and generate graphs on the regularity of intake.